2015
DOI: 10.1016/j.pmrj.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Development of New or Worsened Pressure Ulcers Among Patients in Inpatient Rehabilitation Facilities in the United States: Data From the Uniform Data System for Medical Rehabilitation

Abstract: Admission FIM total and CMS comorbidity tier may be useful in the identification of patients at risk for development of new or worsened pressure ulcers in IRFs. Identification of pressure ulcer risk factors has important implications for individual plan-of-care decisions as well as for resource provisions during the rehabilitation stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
10
0
4
Order By: Relevance
“…The use of medical devices including cords from oxygen supplying respirators, tracheostomy cannula, and tubing cause compression of facial and neck skin tissue, predisposing to the development of PU [43]. The relative risk (RR) of pressure ulcers among patients with CPD in a rehabilitation unit was found to be 1.92 [44]. Margolis et al [19] reported that the prevalence of CPD was 9.0% in older adults in the community and the adjusted RR for PU was 1.24.…”
Section: Resultsmentioning
confidence: 99%
“…The use of medical devices including cords from oxygen supplying respirators, tracheostomy cannula, and tubing cause compression of facial and neck skin tissue, predisposing to the development of PU [43]. The relative risk (RR) of pressure ulcers among patients with CPD in a rehabilitation unit was found to be 1.92 [44]. Margolis et al [19] reported that the prevalence of CPD was 9.0% in older adults in the community and the adjusted RR for PU was 1.24.…”
Section: Resultsmentioning
confidence: 99%
“…8 Considerable research has focused on the identification of risk factors, prevention and treatment of PrU; however, PrU remain one of the most prevalent and devastating sequelae of SCI, with costly complications and hospitalizations in common. [9][10][11][12][13][14][15] The risk of PrU is multifactorial. A substantial number of systematic reviews have addressed the risk factors 10,11,14,16,17 as well as prevention and treatment of PrU.…”
Section: Introductionmentioning
confidence: 99%
“…Estudo realizado com objetivo de avaliar os fatores de risco para ocorrência de lesão por pressão em indivíduos com sequelas de diversas doenças (acidente vascular cerebral, traumatismo cranioencefálico, amputação de membros inferiores, lesão medular, entre outras), durante a reabilitação, mostrou que os indivíduos com lesão medular e amputados apresentam alto risco para ocorrência de lesão por pressão e baixo escore na Escala de Medida de Independência Funcional, fator de risco significante para ocorrência de lesão por pressão neste grupo, durante a reabilitação (29) . Este achado vem ao encontro com os resultados desta revisão, em que dois estudos evidenciaram este fator de risco para ocorrência de lesão por pressão, durante a etapa de reabilitação neurológica (15)(16) .…”
Section: Discussionunclassified